2022
DOI: 10.33225/jbse/22.21.836
|View full text |Cite
|
Sign up to set email alerts
|

Developing Communication Competence in Digital Learning Environments for Primary Science Students

Abstract: Effective natural science teaching in primary schools helps students to form and change their conceptions about nature and natural processes. This is only possible through communicating about learners’ existing misconceptions and the process of transforming them into correct scientific concepts – using a socio-constructivist learning approach. The aim of this study was to find out what happens when the natural science teaching/learning process moves into digital learning environments. Immediately after the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
0
0
Order By: Relevance
“…As part of research question 1, it was explored which digital competences predominate among younger students. The results of the study showed that younger students have significantly lower competencies in using the Internet than the students of higher grades, which is related to both basic computer skills and the skills children need for successful online learning, which is consistent with previous research, for example, by researchers Delgado et al (2018), Legvart et al (2021) and Legvart et al (2022). Forzani and Leu (2012, p. 6) said that students need to start learning new literacy skills early if they are to adopt them by adulthood, which is not only necessary for them, but will also determine their future.…”
Section: Discussionsupporting
confidence: 90%
“…As part of research question 1, it was explored which digital competences predominate among younger students. The results of the study showed that younger students have significantly lower competencies in using the Internet than the students of higher grades, which is related to both basic computer skills and the skills children need for successful online learning, which is consistent with previous research, for example, by researchers Delgado et al (2018), Legvart et al (2021) and Legvart et al (2022). Forzani and Leu (2012, p. 6) said that students need to start learning new literacy skills early if they are to adopt them by adulthood, which is not only necessary for them, but will also determine their future.…”
Section: Discussionsupporting
confidence: 90%
“…Also, the interpretation of the data is often inadequate, insufficient, and amateurish; much of the data is outdated, which means that long and deep reading skills are required for successful reading and learning about ecological issues. Even adult, more experienced readers often cannot navigate the mass of information, and this is especially true for younger students (Legvart et al, 2021;Legvart et al, 2022).…”
Section: Research Problemmentioning
confidence: 99%
“…Zato izpostavljamo, da je raba družbenega omrežja Facebook, kot smo jo zastavili v pričujoči raziskavi, načrtovana za poglabljanje doživetja in ne za interpretacijo obravnavane učne vsebine. Ne glede na to, da smo opazovali tudi cilje prvega vzgojno-izobraževalnega obdobja, pa uporabe družbenih omrežij (vsaj) v zgodnjem obdobju šolanja ne priporočamo niti učenci za to nimajo zadostnih digitalnih kompetenc (Kerneža in Kordigel, 2022;Legvart et al, 2022).…”
Section: Diskusijaunclassified